Morbidity and immediate outcome of Small for Gestational Age infants born at term gestation - Khanal, Sagun; Gupta, Veena; Dahal, Ashish (Journal of Karnali Academy of Health Sciences, 2024)
Background: Small-for-gestational-age (SGA) is defined as birth weight below the tenth percentile according to a specific gestational age and sex reference. SGA babies are either due to symmetric or asymmetric intrauterine growth restriction.Objectives: The study aims to evaluate the immediate outcome of the full term SGA neonates requiring neonatal intensive care unit (NICU) admission. Methods: It was prospective cross-sectional study conducted between February 2018 and January 2019 in NICU of Nepalgunj Medical College Teaching Hospital, Kohalpur, Banke. Babies were evaluated daily for short term outcome till they were discharged from hospital.Results: A total of 50 term SGA babies were included in the study. Most of the SGA babies needing admission to NICU were severe intrauterine growth restriction (IUGR). Among 50 cases 22 were male and 22 were female. Meconium-stained liquor was present in 20% during birth. Eighty two percent cried immediately, 4% cried after stimulation, 12% needed bag and mask ventilation and 2% were intubated at birth. The short term morbidities during NICU stay were birth asphyxia (14%), apnoea (8%), jaundice (30%), bleeding (2%), meconium aspiration syndrome (10%), neonatal sepsis (44%), transient tachypnoea of newborn (12%), hypoglycemia (6%). Four of the SGA babies expired due to severe sepsis. Asymmetrical intrauterine growth retardation (IUGR) babies were in 44% and symmetrical IUGR were in 56%. There was no significant difference in outcome of symmetrical and asymmetrical babies. Their final outcome was 92% discharged and 8% death.Conclusions: Most of the SGA babies needing admission to NICU were severe IUGR. The most common morbidities seen was Neonatal sepsis followed by neonatal jaundice. The result of this study could be important to recognize the anticipated problems and areas requiring attention to improve quality of neonatal care of SGA babies in order to manage the problems associated with them.